Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/mnras/stt1038
|View full text |Cite
|
Sign up to set email alerts
|

Environment-derived constraints on the progenitors of low-luminosity Type I supernovae★

Abstract: We present a study of the properties of the host galaxies of unusual transient objects of two types, both being sub-luminous compared with the major classes of supernovae. Those of one type exhibit unusually strong calcium features, and have been termed 'Ca-rich'. Those of the second type, with SN2002cx as the prototype and SN2008ha as the most extreme example to date, have some properties in common with the first, but show typically lower ejecta velocities, and different early spectra. We confirm important di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
102
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 40 publications
10
102
1
Order By: Relevance
“…Investigations into their environments seem to imply relatively young progenitors. Lyman et al (2013) showed that SNe Iax have a similar degree of association to host galaxy on-going SF as SNe IIP, and used this to argue for progenitors with delay times of less than 50 Myrs. It is interesting to note that Foley et al (2014) constrained the progenitor lifetime of the extreme SN Iax SN 2008ha to be less than 80 Myrs.…”
Section: Sne Iaxmentioning
confidence: 99%
“…Investigations into their environments seem to imply relatively young progenitors. Lyman et al (2013) showed that SNe Iax have a similar degree of association to host galaxy on-going SF as SNe IIP, and used this to argue for progenitors with delay times of less than 50 Myrs. It is interesting to note that Foley et al (2014) constrained the progenitor lifetime of the extreme SN Iax SN 2008ha to be less than 80 Myrs.…”
Section: Sne Iaxmentioning
confidence: 99%
“…Nevertheless, the undisputed presence of spectral lines due to hydrogen in these type II-Plateau SNe, and the conspicuous absence of these in SNe Iax, including SN 2008ha, poses problems for this scenario. Recent studies that have considered the location of SNe Iax within their host galaxies have shown that SNe Iax tend to favour late-type galaxies with higher local star formation rates, which could indicate that they result from younger stars (Lyman et al 2013). Some progenitor channels involving WDs in binary systems are, however, consistent with the relatively young ages inferred for SNe Iax progenitors (Wang et al 2014;Kromer et al 2015) implying that environmental factors alone cannot be used as a discriminating factor.…”
Section: Introductionmentioning
confidence: 96%
“…Even more striking, many are found at substantial offsets from their presumed host galaxies, suggesting either that they originate in extremely faint systems (such as globular clusters; Yuan et al 2013), or alternatively that the progenitor has traveled from its birth site. Increasingly deep limits at the transient locations have failed to detect an underlying host system, favoring the latter interpretation (Lyman et al 2013(Lyman et al , 2014(Lyman et al , 2016.…”
Section: Introductionmentioning
confidence: 99%